Factors Influencing the Choice of Value Addition Among Kiwi Growers in Ilam, Nepal - Magar, P.; Singh, O.P.; Bhatta, S.; Giri, D.R.; Sapkota, S.; Mishra, B.P. (NPI Journal of Science and Technology, 2024)
Value addition helps farmer to overcome financial difficulties during market crises. Production of value-added product is the best possible alternative to diversify income sources for farmers in developing countries like Nepal. However, the choice of value addition is low among kiwi growers in Nepal. An investigation was carried out to identify existing value-added products and factors influencing the choice of value addition among kiwi growers in Ilam district, Nepal. Primary data were gathered using a pretested semi-structured questionnaire with 39 randomly selected kiwi growers from the study area during 2023, followed by Focus Group Discussion and Key Informant Interview with selected individuals. Descriptive statistics and a logit model were used to analyze the findings of the study. The results revealed that juice was the commonly produced product. Farm size was statistically significant in production of value-added products. Thus, extension agencies of government and non-governmental organizations should primarily focus on large farms for better adoption of value addition. Similarly, provisions to increase farm sizes can be made by providing cost-effective lease in options or even subsidies to lease in land. Group based farming enterprises should be promoted to increase the adoption.